1997
DOI: 10.1002/(sici)1097-4547(19970815)49:4<461::aid-jnr7>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms for inhibition of cell proliferation via cell cycle proteins in PC12 cells by nerve growth factor and staurosporine

Abstract: PC12 cells have previously been shown to cease cell division during nerve growth-factor (NGF)-induced differentiation by affecting specific cell cycle proteins. Staurosporine, a protein kinase inhibitor, also causes PC12 cell differentiation, independently of neurotrophins or plasma membrane receptors. We have investigated the relationship of the tumor suppressor protein, p53, and other cell cycle proteins to the antiproliferative effects of NGF and staurosporine in PC12 cells. NGF treatment of PC12 cells stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 58 publications
7
26
0
Order By: Relevance
“…As shown here, NGF-activated p53 binds to the p21 Waf1/Cip1 promoter and activates its transcription. Furthermore, p21 Waf1/Cip1 protein levels were highly increased with NGF alone as previously described [9,57]. NGF may therefore prime PC12 cells for survival by increasing levels of the antiapoptotic factors p21 Waf1/Cip1 and Bcl-2 during differentiation.…”
Section: Discussionsupporting
confidence: 76%
“…As shown here, NGF-activated p53 binds to the p21 Waf1/Cip1 promoter and activates its transcription. Furthermore, p21 Waf1/Cip1 protein levels were highly increased with NGF alone as previously described [9,57]. NGF may therefore prime PC12 cells for survival by increasing levels of the antiapoptotic factors p21 Waf1/Cip1 and Bcl-2 during differentiation.…”
Section: Discussionsupporting
confidence: 76%
“…To confirm this, the induction of growth-associated protein 43 (GAP-43) and p21 was examined by Western blot analysis. GAP-43 is a neuronal differentiation marker whose expression directly correlates with the extent of differentiation, while p21 is required for the cell cycle arrest mediated by NGF during differentiation (14,41). We showed that GAP-43 was induced in an NGF-dependent manner ( Fig.…”
Section: Vol 27 2007mentioning
confidence: 66%
“…These contradictory findings may be related to differ- ences in culture conditions which affect both the extent of differentiation and the expression of cell cycle-associated proteins. For measurements of p21 WAF1 promoter activity, we treated the PC12 cells for 3 days in defined medium, which considerably speeds both NGF-induced differentiation (27) and induction of p21 WAF1 (62). The other group treated their cells for only 2 days in serum-containing medium.…”
Section: Discussionmentioning
confidence: 99%